Pengaruh Perceived Value dan Harga Terhadap Minat Belangganan Spotify Premium Yang Dimoderasi Oleh Usia Pengguna - Noi Gitas Syahlita; Wina Driyan Pradana (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to determine the effect of perceived value and price on interest in subscribing to Spotify Premium in Indonesia and to test the moderating effect of user age on the model. This study uses a quantitative approach with a non-probability sampling technique (purposive sampling method), involving a total of 118 respondents from Spotify Premium users in Indonesia who belong to the millennial generation and generation Z. For data analysis, this study uses SmartPLS software version 4. The results showed that the variables of perceived value and price can influence the interest in subscribing to Spotify Premium, and the variable of user age (millennial generation and generation Z) can moderate the relationship between the three variables.